Transboundary COVID-19 response on health communication in Botswana, South Africa and Zimbabwe - Nyandoro, Mark; Mduluza, Takafira; Nyandoro, Lucy (AOSIS, 2024)
A global COVID-19 pandemic caused untold community disruptions, a huge toll on lives and placed major burdens on the economies of developing countries. It spread worldwide within a short period of time before nations could mobilise evidence for the best responses. Communities in Botswana, South Africa and Zimbabwe were heavily disrupted. This article focuses on exploring the transboundary differences in COVID-19 responses, plus the implications for improving the health communication strategies in a pandemic age. Health practitioners and governments were ill-prepared to inform the general public about the pandemic and enforced complete shutdowns of economic and social activities. With the COVID-19 pandemic ravaging communities, there was a dearth of focused health communication on COVID-19’s end. New tools of communication and dissemination of information were embraced in the southern Africa country-specific cases. For example, content on precautionary lifestyles, individual or personal responsibility and utilisation of community health workers in the pandemic era was prioritised to prevent or minimise infections and avoid recurrence of the disease. New communication methods were important for addressing uncertainty and can be applied for any future pandemic. This health communication topic addresses the neglected, but important gap on the efficacy of processes towards better health communication strategies. The transdisciplinary methods include improved health communication strategies informed by the experiences of three Southern African Development Community countries. While such measures to arrest COVID-19 proved plausible, these countries’ projections for the future are a concern, suggesting an urgent need to enhance and strengthen health communication in southern Africa. Transdisciplinary contribution: This is a transdisciplinary exploration of health communication and its implications for COVID-19 and future pandemic responses in Botswana, South Africa and Zimbabwe.
Keywords: COVID-19; health communication; communities; efficacy; health communication; information packages; pandemic